Anxiety Among Community-Dwelling U.S. Chinese Older Adults - Dong, XinQi (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND. This study aimed to explore the prevalence and correlates of anxiety disorders and any anxiety symptoms among community-dwelling U.S. Chinese older adults. METHODS. Guided by a community-based participatory research approach, 3,159 community-dwelling Chinese older adults in the Greater Chicago area were interviewed in person between 2011 and 2013. RESULTS. Of 3,159 older adults surveyed, 8.5% had anxiety disorders and 65.0% reported having any anxiety symptoms. Being female, unmarried, poorer health status, lower quality of life, and worsening health over the past year were positively correlated with anxiety disorders and any anxiety symptoms. Living with fewer people and having fewer children were only correlated with any anxiety symptoms and lower income was only correlated with anxiety disorders. CONCLUSIONS. This study emphasizes that interventions for anxiety among Chinese older adults should give special attention to older women, those who are unmarried, with impaired health status, and poorer quality of life. Further longitudinal studies should be conducted to better understand risk factors and outcomes associated with anxiety among U.S. Chinese older adults.